Investigation of the frequency dependent spatio-temporal dynamics and controllability of microdischarges in unipolar pulsed plasma electrolytic oxidation - Hermanns, Patrick; Boeddeker, Simon; Bracht, Vera; Bibinov, Nikita; Grundmeier, Guido; Awakowicz, Peter (Journal of Physics D: Applied Physics)

Multilayer coatings based on the combination of perfluorinated organosilanes and nickel films for injection moulding tools - Calderón, Juan Carlos; Koch, Leon; Bandl, Christine; Kern, Wolfgang; Jilg, Jannik; Schilp, Catharina; Moritzer, Elmar; Grundmeier, Guido (Surface and Coatings Technology)

Kinetic studies of cathode degradation as caused by ice formation in MEAs - Liphardt, L.; Disson, S.; Suematsu, K.; Grundmeier, Guido (International Journal of Hydrogen Energy)

Investigation of the passive layer on a solid-state sintered silicon carbide ceramic formed in sulfuric acid - Schneider, M.; Kremmer, K.; Voigt, M.; Grundmeier, Guido (Corrosion Science)

Design and Objective Evaluation of Filter- and Optimization-based Motion Cueing Strategies for a Hybrid Kinematics Driving Simulator with 5 Degrees of Freedom - Biemelt, Patrick; Gausemeier, Sandra; Trächtler, Ansgar (International Journal On Advances in Systems and Measurements)

Design and Evaluation of a Novel Filter-Based Motion Cueing Strategy for a Hybrid Kinematics Driving Simulator with 5 Degrees of Freedom - Biemelt, Patrick; Mertin, Sven; Rüddenklau, Nico; Gausemeier, Sandra; Trächtler, Ansgar (Proceedings of the Driving Simulation Conference Europe VR)

Macroscopic Traffic Flow Control using Consensus Algorithms - Mertin, Sven; Malena, Kevin; Link, Christopher; Gausemeier, Sandra; Trächtler, Ansgar (The 23rd IEEE International Conference on Intelligent Transportation Systems)

Real-Time Optimized Model Predictive Control of an Active Roll Stabilization System with Actuator Limitations - Nareyko, Georgi; Biemelt, Patrick; Trächtler, Ansgar (Proceedings of the 21st IFAC World Congress)

A Model-Based Online Reference Prediction Strategy for Model Predictive Motion Cueing Algorithms - Biemelt, Patrick; Link, Christopher; Gausemeier, Sandra; Trächtler, Ansgar (Proceedings of the 21st IFAC World Congress)

Echtzeitfähige Planung optimierter Trajektorien für sensorgeführte, kinematisch redundante Mechanismen auf einer Industriesteuerung - Schütz, Stefan; Rüting, Arne Thorsten; Henke, Christian; Trächtler, Ansgar (Entwurf komplexer Automatisierungssysteme (EKA))

Language-agnostic Injection Detection - Hermerschmidt, Lars; Straub, Andreas; Piskachev, Goran (2020 IEEE Security and Privacy Workshops (SPW))

SWAN_ASSIST: Semi-Automated Detection of Code-Specific, Security-Relevant Methods - Piskachev, Goran; Nguyen Quang Do, Lisa; Johnson, Oshando; Bodden, Eric (2019 34th IEEE/ACM International Conference on Automated Software Engineering (ASE))

AuthCheck: Program-State Analysis for Access-Control Vulnerabilities - Piskachev, Goran; Petrasch, Tobias; Späth, Johannes; Bodden, Eric (Lecture Notes in Computer Science)

Wood-based materials as a sustainable alternative for future car body construction - Schweizer, Swetlana; Akbulut Irmak, Emine Fulya; Tröster, Thomas

Two-dimensional electron bound hole photoluminescence in GaAs in perpendicular magnetic fields - Schuster, J; Kim, T Y; Batke, E; Reuter, Dirk; Wieck, A D (Semiconductor Science and Technology)

Strain-driven InAs island growth on top of GaAs(111) nanopillars - Riedl, T.; Kunnathully, V. S.; Trapp, A.; Langer, T.; Reuter, Dirk; Lindner, J. K. N. (Physical Review Materials)

Kernel-Based Approximation of the Koopman Generator and Schrödinger Operator - Klus, Stefan; Nüske, Feliks; Hamzi, Boumediene (Entropy)
Many dimensionality and model reduction techniques rely on estimating dominant eigenfunctions of associated dynamical operators from data. Important examples include the Koopman operator and its generator, but also the Schrödinger operator. We propose a kernel-based method for the approximation of differential operators in reproducing kernel Hilbert spaces and show how eigenfunctions can be estimated by solving auxiliary matrix eigenvalue problems. The resulting algorithms are applied to molecular dynamics and quantum chemistry examples. Furthermore, we exploit that, under certain conditions, the Schrödinger operator can be transformed into a Kolmogorov backward operator corresponding to a drift-diffusion process and vice versa. This allows us to apply methods developed for the analysis of high-dimensional stochastic differential equations to quantum mechanical systems.

Posthuman Dystopia: Animal Surrealism and Permanent Crisis in Contemporary British Theatre - Tönnies, Merle; Voigts, Eckart (Journal of Contemporary Drama in English)

Bilingual education in monolingual contexts: a comparative perspective - Rumlich, Dominik (The Language Learning Journal)

Englischsprachige Jugendbücher innerhalb und außerhalb des Englischunterrichts – Young Adult Fiction als empirischer Gegenstand der Literaturdidaktik - Matz, Frauke; Rumlich, Dominik (KONTROVERS. Literaturdidaktik meets Literaturwissenschaft)

Die mündliche Prüfung in der Sekundarstufe II: Herausforderung und Chance für die Fremdsprachendidaktik - Matz, Frauke; Rogge, Michael; Rumlich, Dominik (Testen bildungssprachlicher Kompetenzen und akademischer Sprachkompetenzen – Zugänge für Schule und Hochschule)

Softwareentwicklung wie am Fliessband - Koch, Thorsten; Meyer, Matthias; Fazal-Baqaie, Masud; Runschke, Hubert (Software Engineering 2020 (SE 2020))

Entwurf eines Simulationsmodells zur Bewertung des Betriebsverhaltens von elektromechanischen Spindelhubantrieben - Tominski, J.; Zimmer, Detmar (Konstruktion - Zeitschrift für Produktentwicklung und Ingenieur-Werkstoffe)
Simulationsmethoden bieten die Möglichkeit, instabile Betriebszustände von Antriebssystemen noch vor dem Einsatz in einer realen Anwendung zu identifizieren und gezielt Gegenmaßnahmen abzuleiten. In dem vorliegenden Artikel wird die Entwicklung eines Simulationsmodells für elektro- mechanische Spindelhubantriebe beschrieben. Im Fokus der Betrachtung stehen insbesondere reibungsinduzierte Schwingphänomene, die in Schneckengetrieben und Trapezgewindespindeln entstehen können. Das Simulationsmodell wird anhand von experimentellen Messungen für mehrere stabile Betriebspunkte und für einen instabilen Betriebszustand validiert. Eine Diskussion der Ergebnisse schließt den Beitrag ab.

Spatially resolved light field analysis of the second-harmonic signal of χ(2)-materials in the tight focusing regime - Spychala, K. J.; Mackwitz, P.; Widhalm, A.; Berth, G.; Zrenner, A. (Journal of Applied Physics)

Spatially resolved light field analysis of the second-harmonic signal of χ(2)-materials in the tight focusing regime - Spychala, K. J.; Mackwitz, P.; Widhalm, A.; Berth, Gerhard; Zrenner, Artur (Journal of Applied Physics)

Software tools for business model innovation: Current state and future challenges - Szopinski, Daniel; Schoormann, T.; John, Thomas; Knackstedt, R.; Kundisch, Dennis (Electronic Markets)

Ancillary market signaling: A two-stage model of economic reputation on ancillary market success - Kaimann, Daniel (Applied Economics Letters)

Extractive Snippet Generation for Arguments - Alshomary, Milad; Düsterhus, Nick; Wachsmuth, Henning (Proceedings of 43rd International ACM SIGIR Conference on Research and Development in Information Retrieval)

Transient Bodies in Anglophone Literature and Culture

Modulations of Inter-Hemispherical Phase Coupling in Human Single Leg Stance. - Lehmann, T; Büchel, D; Cockcroft, J; Louw, Q; Baumeister, Jochen (Neuroscience)

Electrocortical dynamics differentiate athletes exhibiting low- and high- ACL injury risk biomechanics. - Bonnette, S; Diekfuss, JA; Grooms, DR; Kiefer, AW; Riley, MA; Riehm, C; Moore, C; Barber Foss, KD; DiCesare, CA; Baumeister, Jochen; Myer, GD (Psychophysiology)

Country-by-Country Reporting Goes Public - Cui Bono? - Lagarden, Martin; Schreiber, Ulrich; Simons, Dirk; Sureth-Sloane, Caren (International Transfer Pricing Journal)
After the introduction of CbCR – pursuant to the BEPS Project (Action 13) in 2015 –, which was established to reduce the information asymmetry between MNEs and tax authorities of the countries they operate in, now public CbCR – as suggested by the EU Commission in 2016 – is discussed as a next step. Here, the objective is to overcome information asymmetries between MNEs and the general public of the countries they operate in. Starting from the assumption that regulators care about the legitimacy of tax laws, this article evaluates pros and cons of public CbCR. The authors find that from the perspective of information asymmetries, public CbCR increases tax transparency only marginally at best. Accordingly, it is concluded that democracies that are based on the rule of law seem to rely on pillories in terms of public CbCR to enforce fair tax payments.

Privacy-Preserving Incentive Systems with Highly Efficient Point-Collection - Bobolz, Jan; Eidens, Fabian; Krenn, Stephan; Slamanig, Daniel; Striecks, Christoph (Proceedings of the 15th ACM Asia Conference on Computer and Communications Security (ASIA CCS ’20),)

Inwiefern können Praxisphasen im Studium zu einer Theorie-Praxis-Relationierung beitragen? Implikationen für die professionelle Entwicklung angehender Lehrkräfte. - Harteis, Christian; Caruso, Carina (Verlängerte Praxisphasen in der universitären Lehrerbildung: Spannungsfelder zwischen Theorie, Praxis und der Bestimmung von Professionalisierung)

Challenges in Model-Driven Development of Multi-Platform Augmented Reality Applications - Jovanovikj, Ivan; Yigitbas, Enes; Sauer, Stefan; Engels, Gregor (Softwaretechnik-Trends, Proceedings of the 22st Workshop Software-Reengineering & Evolution (WSRE) & 11h Workshop Design for Future (DFF))

Higher Income, Larger Loan? Monotonicity Testing of Machine Learning Models - Sharma, Arnab; Wehrheim, Heike (Proceedings of the ACM SIGSOFT International Symposium on Software Testing and Analysis (ISSTA).)

Algorithm Selection for Software Validation Based on Graph Kernels - Richter, Cedric; Hüllermeier, Eyke; Jakobs, Marie-Christine; Wehrheim, Heike (Journal of Automated Software Engineering)

Dynamic Provisioning of Network Services on Heterogeneous Resources - Razzaghi Kouchaksaraei, Hadi; Shivarpatna Venkatesh, Ashwin Prasad; Churi, Amey; Illian, Marvin; Karl, Holger (European Conference on Networks and Communications (EUCNC 2020))

Designing Digital Community Service Platforms for Crowd-Based Services in Urban Areas - Bartelheimer, Christian; Wolf, Verena; Langhorst, Nico; Seegers, Florian (Proceedings of the 15th International Conference on Design Science Research in Information Systems and Technology)

Seven Paradoxes of Business Process Management in a Hyper-Connected World - Beverungen, Daniel; Buijs, Joos C. A. M.; Becker, Jörg; Di Ciccio, Claudio; van der Aalst, Wil M. P.; Bartelheimer, Christian; vom Brocke, Jan; Comuzzi, Marco; Kraume, Karsten; Leopold, Henrik; Matzner, Martin; Mendling, Jan; et al. (Business & Information Systems Engineering)

PS³—A Domain-specific Modeling Language for Platform-based Smart Service Systems - Lüttenberg, Hedda (Designing for Digital Transformation. Co-Creating Services with Citizens and Industry. DESRIST 2020)

Metasurfaces help lasers to mode-lock - Sain, Basudeb; Zentgraf, Thomas (Light: Science & Applications)

Density and Thermodynamic Speed of Sound of Liquid Vinyl Chloride - Javed, Muhammad Ali; Rüther, Moritz; Baumhögger, Elmar; Vrabec, Jadran (Journal of Chemical & Engineering Data)

What Are We Talking About When We Talk About Technology Pivots? – A Delphi Study - Bohn, Nicolai; Kundisch, Dennis (Information & Management)

The Shanghai-Hong Kong Stock Connect: An Application of the Semi-CGARCH and Semi-EGARCH - Peitz, Christian; Feng, Yuanhua; Gilroy, Bernard Michael; Stöckmann, Nico (Asian Economic and Financial Review)

Die Niedrigzinspolitik der Europäischen Zentralbank - Gilroy, Bernard Michael; Peitz, Christian (WISU – Das Wirtschaftsstudium)

Survey on Algorithms for Self-Stabilizing Overlay Networks - Feldmann, Michael; Scheideler, Christian; Schmid, Stefan (ACM Computing Surveys)
The maintenance of efficient and robust overlay networks is one of the most fundamental and reoccurring themes in networking. This paper presents a survey of state-of-the-art algorithms to design and repair overlay networks in a distributed manner. In particular, we discuss basic algorithmic primitives to preserve connectivity, review algorithms for the fundamental problem of graph linearization, and then survey self-stabilizing algorithms for metric and scalable topologies. We also identify open problems and avenues for future research.

Time- and Space-Optimal Discrete Clock Synchronization in the Beeping Model - Feldmann, Michael; Khazraei, Ardalan; Scheideler, Christian (Proceedings of the 32nd ACM Symposium on Parallelism in Algorithms and Architectures (SPAA))
We consider the clock synchronization problem in the (discrete) beeping model: Given a network of $n$ nodes with each node having a clock value $δ(v) \in \{0,… T-1\}$, the goal is to synchronize the clock values of all nodes such that they have the same value in any round. As is standard in clock synchronization, we assume arbitrary activations for all nodes, i.e., the nodes start their protocol at an arbitrary round (not limited to $\{0,…,T-1\}$). We give an asymptotically optimal algorithm that runs in $4D + \Bigl\lfloor \frac{D}{\lfloor T/4 \rfloor} \Bigr \rfloor · (T \mod 4) = O(D)$ rounds, where $D$ is the diameter of the network. Once all nodes are in sync, they beep at the same round every $T$ rounds. The algorithm drastically improves on the $O(T D)$-bound of \cite{firefly_sync} (where $T$ is required to be at least $4n$, so the bound is no better than $O(nD)$). Our algorithm is very simple as nodes only have to maintain $3$ bits in addition to the $\lceil \log T \rceil$ bits needed to maintain the clock. Furthermore we investigate the complexity of self-stabilizing solutions for the clock synchronization problem: We first show lower bounds of $Ω(\max\{T,n\})$ rounds on the runtime and $Ω(\log(\max\{T,n\}))$ bits of memory required for any such protocol. Afterwards we present a protocol that runs in $O(\max\{T,n\})$ rounds using at most $O(\log(\max\{T,n\}))$ bits at each node, which is asymptotically optimal with regards to both, runtime and memory requirements.

Mechanisms, Preferences, and Heterogeneity in Matching Markets - Stroh-Maraun, Nadja

Polarization-Encrypted Orbital Angular Momentum Multiplexed Metasurface Holography - Zhou, Hongqiang; Sain, Basudeb; Wang, Yongtian; Schlickriede, Christian; Zhao, Ruizhe; Zhang, Xue; Wei, Qunshuo; Li, Xiaowei; Huang, Lingling; Zentgraf, Thomas (ACS Nano)